2001
DOI: 10.1175/1520-0442(2001)014<1697:lioeno>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Indices of El Niño Evolution

Abstract: To characterize the nature of El Niño-Southern Oscillation (ENSO), sea surface temperature (SST) anomalies in different regions of the Pacific have been used. An optimal characterization of both the distinct character and the evolution of each El Niño or La Niña event is suggested that requires at least two indices: (i) SST anomalies in the Niño-3.4 region (referred to as N3.4), and (ii) a new index termed here the Trans-Niño Index (TNI), which is given by the difference in normalized anomalies of SST between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
656
0
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 878 publications
(699 citation statements)
references
References 14 publications
31
656
0
12
Order By: Relevance
“…The MEI cannot differentiate between 'different flavours' of El Niño (Trenberth and Stepaniak, 2001), or weigh in on the debate whether there are fundamentally different so-called Eastern-Pacific versus Central-Pacific events (Kao and Yu, 2009). It was ironic to witness the very first El Niño after Rasmusson and Carpenter (1982) described the 'canonical sequence' of El Niño events as a westward propagating phenomenon from the eastern Pacific, to be the 1982-1983 'Super-El Niño' that propagated eastward from the Central Pacific.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The MEI cannot differentiate between 'different flavours' of El Niño (Trenberth and Stepaniak, 2001), or weigh in on the debate whether there are fundamentally different so-called Eastern-Pacific versus Central-Pacific events (Kao and Yu, 2009). It was ironic to witness the very first El Niño after Rasmusson and Carpenter (1982) described the 'canonical sequence' of El Niño events as a westward propagating phenomenon from the eastern Pacific, to be the 1982-1983 'Super-El Niño' that propagated eastward from the Central Pacific.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…It was ironic to witness the very first El Niño after Rasmusson and Carpenter (1982) described the 'canonical sequence' of El Niño events as a westward propagating phenomenon from the eastern Pacific, to be the 1982-1983 'Super-El Niño' that propagated eastward from the Central Pacific. There were several more events of this type since then, most prominently the 1986-1988 and 1991-1995 events, leading some to proclaim that there had been a fundamental shift in behaviour (Trenberth and Stepaniak, 2001). For the newer record, we can confirm that central Pacific events tend to start later in the calendar year than eastern-Pacific events (Kao and Yu, 2009), but found that most events of either type end up becoming basin-wide nevertheless, rendering their distinction less meaningful once fully established.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The data base, spanning from January 1910 to December 2011 in monthly time steps, has a spatial resolution of 2 × 2º. We excluded iced-oceans by extracting data only from 70º S to 70º N. From the same website we downloaded the time series of the Atlantic Multidecadal Oscillation (AMO; Enfield et al, 2001), the Pacific Decadal Oscillation (PDO; Mantua et al, 1997), and the Trans Niño Index (TNI; Trenberth and Stepaniak, 2001), and plotted them with a five year moving average filter to explore similarities in the variability patterns.…”
Section: Methodsmentioning
confidence: 99%
“…The ±0.5°C threshold is consistent with the ONI. Following Trenberth (1997), a threshold sensitivity analysis was carried out for the ±0.4°C ENSO definition given by Trenberth (1997) and Trenberth and Stepaniak (2001) to allow event-capture discrepancies to be investigated.…”
Section: Oceanic Component Of Enso; El Niñomentioning
confidence: 99%
“…This was derived from the HadISST (Hadley Centre Sea Ice and Sea Surface Temperature) dataset using 1°× 1°l atitude/longitude grids with all area averages and interpolation computations calculated at full resolution (Trenberth and Stepaniak, 2001). The period of overlap between observational and reconstructed SSTs was analysed to assess the ability of the latter to serve as a reliable pre-instrumental surrogate, details of which are found in Section 3.1.…”
Section: Oceanic Component Of Enso; El Niñomentioning
confidence: 99%